Perlindungan Konsumen Terhadap Tindakan Pemadaman Listrik yang dilakukan Secara Sepihak Oleh PT. PLN (Persero) UP3 Bali Selatan - I Gede Dharma Kusuma; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2021)
Indonesia is a country consisting of several islands and every region that requires electricity as a daily need and long -term needs, the current situation many people complain about the services provided by PLN is a power outage without prior notice. The numb er of public complaints related to power outages makes PLN in improving the organizational structure, especially in the sector of coordination between workers. The government in terms of providing protection to the community in terms of obtaining electricity supply is enough to make consumer protection regulations in which there is a right and obligation of consumers to get justice and obliged to conduct appeals from the government in an effort to prevent criminal acts in accordance with positive laws appli cable in Indonesia. The government is questioning the field workers from the PLN who deliberately or unintentionally do not inform the public of this turn -based power outage and it should be the PLN to give a reprimand for its workers who do not carry out orders in accordance with the SOP applicable in the company.